A gene coding for tRNA(Val) is located near 5′ terminus of 16S rRNA gene in Zea mays chloroplast genome - Schwarz, Z. (1981)
A region of 635 base pairs preceding a gene for 16S rRNA in the Zea mays chloroplast genome has been mapped and its sequence has been determined. Screening for structural elements common to tRNAs reveals a gene coding for tRNA(Val) (GU(U)(C)) positioned 303 base pairs proximal to the 5′ end of the 16S rRNA gene. Both the tRNA(Val) and the 16S rRNA are coded in the same DNA strand. The tRNA nucleotide sequence predicted from the DNA sequence meets all structural characteristics common to tRNA primary and secondary structures. In a quantitative comparison with primary structures of the 14 known tRNA(Val) species the chloroplast isoaceptor shows much higher homology with that from prokaryotic than that from eukaryotic species. Regions that Escherichia coli RNA polymerase protects from nuclease attack are observed 25 and 100 base pairs upstream of the tRNA(Val) gene and 105 base pairs upstream of the 16S rRNA gene. Within these regions are short sequences that are very similar to those in the -35 region of E. coli rrn and that may therefore represent all or parts of transcription initiation signals of the respective genes.